The architecture of visual narrative comprehension: the interaction of narrative structure and page layout in understanding comics - Cohn, Neil (Frontiers in Psychology, 2014)
How do people make sense of the sequential images in visual narratives like comics? A growing literature of recent research has suggested that this comprehension involves the interaction of multiple systems: The creation of meaning across sequential images relies on a “narrative grammar” that packages conceptual information into categorical roles organized in hierarchic constituents. These images units are encapsulated into panels arranged in the layout of a physical page. Finally, how panels frame information can impact both the narrative structure and page layout. Altogether, these systems operate in parallel to construct the gestalt whole of comprehension of this visual language found in comics.